Collaboration among an Academic Institution, Local Communities, and Local Government Units in Protecting Wildlife and Forest Habitats in Southwestern Negros Island, Philippines - Alcala, Ely L.; Hisona, Jireh; Velasco, Joseph Benedict; Dulla, Jemuel (Silliman Journal, 2023)
A community-based forest resource protection program was established in Cauayah and its adjacent areas in southwestern Negros from 2001-2007. The program was preceded by research done by an academic institution, the results of which were used as a basis for establishing the Cauayan watershed reserve, a 6,000ha area that includes the forests of two barangays (villages), Pinamayen and lnayawan. This paper presents the processes employed in establishing a community-based forest protection program and some strategies used to mitigate illegal activities, to improve biodiversity awareness among the stakeholders, and to promote commu-nity and local government participation.